Deaths Associated With Brotizolam Poisoning From a Single Drug Overdose: Four Reported Cases. (March 2018) - Sakai, Kentaro; Saito, Kazuyuki; Takada, Aya; Hikiji, Wakako; Kikuchi, Yosuke; Fukunaga, Tatsushige
Abstract : Abstract: Brotizolam is a short-acting hypnotic in the benzodiazepine family, and fatal poisonings by an overdose of brotizolam are rare. This report describes 4 cases of deaths associated with brotizolam poisoning from a single drug overdose. The ages ranged from 51 to 90 years, and the postmortem interval between death and tissue sampling was 1.5 to 2.5 days. These deaths were classified as 1 homicide and 3 suicides. The concentration of the brotizolam ranged from 0.05 to 0.21 mg/L in the blood samples. Ethanol, which could cause mild alcohol intoxication, was detected in the blood samples from 2 cases. Postmortem examinations did not find any significant pathologic conditions, except for a case of death by drowning in a bathtub due to brotizolam poisoning. These 4 cases suggest that a brotizolam overdose should not be underestimated in terms of its fatal effects, particularly when situations involve alcohol intoxication, injury subsequent to the poisoning, or underlying medical conditions including aging.